The Legal Framework for the Civil Liability of the Robot on the Side: Nature, Basis, and Scope - Attallah, Saja; Benseghir, Mourad (Journal of Legal Sciences, 2026)
The litigating robot represents a modern application of artificial intelligence in the legal field. It assists in analyzing cases, drafting legal memoranda, and accelerating judicial procedures. This technology enhances judicial efficiency and reduces litigation costs. However, its use raises complex legal questions regarding automated litigation. It also creates challenges concerning civil liability for damages caused by robotic advocacy. Traditional civil liability rules appear insufficient to address such damages. In response, the European approach adopts the concept of the “human proxy”. Liability is attributed to the natural person who operates, supervises, or directs the robot. This person is considered legally responsible for the robot’s actions. The study recommends mandatory civil liability insurance for litigating robots. It also proposes establishing a compensation fund for damages not covered by insurance. Finally, it rejects granting the robot independent legal personality, as this would undermine the legal profession and the right of defense.